PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA DAN DUKUNGAN INOVASI TERHADAP INOVASI ORGANISASI PERBANKAN DI KOTA MAGELANG - Muhdiyanto, Muhdiyanto (Jurnal Analisis Bisnis Ekonomi, 2009)
This research aim to know the influence of leadership transformasional to employees performance and also to know the influence of leadership transformasional to employees performance which moderating by discipline. Object research is employees PD. BPR Bapas 69 Regency Magelang and executed in May - July 2009. This sample research as much 52 responder from 60 responder used with the method of purposive sampling. Analyzer used by regression. Result of research indicate that, by simultan is variable of leadership of transformasional and discipline have an effect on to performance. Variable leadership of transformasional and discipline have an effect on to performance of equal to 39,2% while the rest of equal to 60,8% influenced by the other; dissimilar variable which not checked. By parsial there are influence which are positive leadership transformasional to employees performnace. There are influence which are positive and signifikan from interaction of leadership transformasional with the discipline to employees performance.